ARTIFICIAL INTELLIGENCE AND ISLAMIC ECONOMIC LAW: EXPLORING STUDENTS' PERCEPTIONS OF ETHICAL AND SHARIA COMPLIANCE ISSUES - Khairani Hayat Situmorang; Imam Surbakti; Sri Wulan Dari Tri Utami (INTERNATIONAL, Journal of Sharia Business Management, 2026)
The rapid development of Artificial Intelligence (AI) has significantly influenced various sectors, including education, economics, and finance. While AI offers numerous opportunities for improving efficiency and innovation, its implementation also raises ethical and Sharia compliance concerns, particularly within the context of Islamic Economic Law. This study aims to explore students' perceptions of ethical and Sharia compliance issues related to the use of AI in economic and financial activities. Employing a qualitative case study design, the research involved 13 undergraduate students of Islamic Economic Law selected through purposive sampling. Data were collected through semi-structured interviews and analyzed using thematic analysis. The findings revealed five major themes: (1) positive perceptions of AI in learning and economic activities, (2) ethical concerns regarding accuracy, privacy, accountability, and technological dependence, (3) perceptions of AI and Sharia compliance, (4) opportunities for AI implementation in Islamic finance, and (5) challenges and future expectations. The results indicate that students generally perceive AI as a beneficial tool that enhances learning efficiency and supports innovation. However, they emphasize the importance of ensuring ethical use, human oversight, and compliance with Islamic principles such as justice (adl), public welfare (maslahah), transparency, and the avoidance of riba and gharar. The study concludes that students adopt a balanced perspective toward AI, recognizing both its opportunities and potential risks. The findings contribute to the growing discussion on AI, ethics, and Islamic Economic Law while offering practical implications for Islamic higher education and the development of Sharia-compliant AI applications.